How do you simplify #(ax - ay - 2by + 2bx)/(ax - 2bx + 2by + ay)#?

1 Answer
Mar 27, 2018

Answer:

#=>(x-y)/(((a-2b)/(a+2b))x+y)#

Explanation:

I don't think this can be simplified much:

#=>(ax - ay - 2by + 2bx)/(ax - 2bx + 2by + ay)#

I tried the following. I combined coefficients:

#=>((a+2b)x-(a+2b)y)/((a-2b)x+(a+2b)y)#

Then I saw that three out of four terms contained the same coefficient. So I divided by it:

#=>(x-y)/(((a-2b)/(a+2b))x+y)#

I guess this is a little better than the original, because whatever #a# and #b# happen to be, they only influence the one term in the denominator and it's easy to see how with this form.